Evaluasi Kekuatan Daya Dukung Pondasi Bored Pile Dengan Struktur Slab On Pile (Studi Kasus Pada Slab On Pile Sta 14+045 Jalan Tol IKN Paket 3a KKT Kariangau-Karang Joang) - Achmad, S.T., M.T, Karmila; Cholick, Baby Febriyana (JST (Jurnal Sains Terapan), 2025)
This study aims to evaluate the load-bearing capacity and strength of the bored piles based on their dimensions and soil testing parameters. SOP 1 STA 14+065 is part of the IKN Toll Road Package 3A KKT Kariangau-Karangjoang, which uses pile slabs due to the soft soil conditions along the road's alignment. A PDA test was conducted to assess the load-bearing capacity of bored pile foundations with an 800 mm diameter with varying depths. Samples from Pile Points P4 B 131 and P4 B 152 were selected because they did not meet the minimum PDA target of 419.6 tons, raising concerns about potential settlement or even structural failure.The load analysis and calculations on the slab-on-pile structure were performed manually based on SNI 1725:2016 "Loading for Bridges" and SNI 2833:2016 "Bridge Design for Earthquake Loads". The slab-on-pile dimension analysis was assisted by the SAP2000 V.14.2.2 software.The study's results show that the static load-bearing capacity at Point P4 B 131 is 12.87% (36.085 tons) lower than the PDA test result. At Point P4 B 152, the static load-bearing capacity is 39.85% (108.67 tons) higher than the PDA test result. The analysis of the SOP 1 Segment 6 model using SAP2000 V.14.2.2 found that the vertical strength required for Piles P4 B 131 and P4 B 152 is 645.25 kN (65.8 tons) and 435.36 kN (44.4 tons), respectively. The allowable load-bearing capacity available in Piles P4 B 131 and P4 B 152 is 118 tons and 65 tons based on the PDA test, and 103.166 tons and 109.068 tons from static load calculation methods. Keywords : Slab on pile, PDA Test, Bearing capacity, Bored pile, SAP2000